Patient Referrals: Bridging the Gap in a Critical Student-Run Free Clinic Resource - Shilpa Rajagopal; Felicia Fong; Jessica Prom; David Lee (Journal of Student-Run Clinics, 2024)
Background: Patients seeking care at student-run free clinics tend to have complex medical histories and require access to a variety of resources and specialties. Student-run free clinics, as a result, often will collaborate with other organizations, health systems, and interprofessional healthcare workers to provide patients with a wide range of services to meet those needs. Unfortunately, student-run free clinics across disciplines continue to experience difficulties with providing patients with access to referrals comparable to what might be available in traditional fee-for-service settings. Some particular challenges include maintaining longitudinal partnerships with local health systems, ensuring patient follow-up, and holistically meeting a wide spectrum of patient concerns. Each student-run free clinic is unique in its clinical focus and operations, resulting in differing capacities to meet the various needs of their communities.Purpose: To describe generalizable strategies for overcoming challenges related to providing patients with access to referral services based on interprofessional discussions from the “Bridging the Gap” session at the Society of Student-Run Free Clinics 2023 Annual Meeting.Summary: Three main areas to improve referral services were identified: 1) utilizing internal referrals and incorporating data-tracking, 2) developing a community-centered database of healthcare resources and social services, and 3) addressing specific patient needs, including transportation to and from appointments. Future evaluation of these interventions should be completed to determine the efficacy and impact on patient outcomes.